2014
DOI: 10.1177/2050640614542496
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of an abbreviated 13 C‐mixed triglyceride breath test for measurement of pancreatic exocrine function

Abstract: Background: A modified 13 C-mixed triglyceride breath test ( 13 C -MTGT) detects moderate pancreatic exocrine insufficiency noninvasively and reliably, but it requires prolonged breath sampling (6 hours (hr)). Objective: We aimed to investigate whether 13 C -MTGT can be abbreviated, to optimize clinical usability. Methods: We analyzed the 13 C-MTGT of 200 consecutive patients, retrospectively. Cumulative 1-5 hr 13 C-exhalation values were compared with the standard parameter (6-hr cumulative 13 C-exhalation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…Although this test is appealing as a non-invasive test, it requires a substantial time investment from patients (6-8 h) in which they can only have limited activity. A recent study suggested the diagnostic accuracy remains good (sensitivity 88 % and specificity 94 %) when an abbreviated 4 h test was performed, but this requires further validation [24]. The largest problem with the MTBT is that the radiolabelled tracers required for the study are not available worldwide.…”
Section: C-mixed Triglyceride Breath Testmentioning
confidence: 93%
See 1 more Smart Citation
“…Although this test is appealing as a non-invasive test, it requires a substantial time investment from patients (6-8 h) in which they can only have limited activity. A recent study suggested the diagnostic accuracy remains good (sensitivity 88 % and specificity 94 %) when an abbreviated 4 h test was performed, but this requires further validation [24]. The largest problem with the MTBT is that the radiolabelled tracers required for the study are not available worldwide.…”
Section: C-mixed Triglyceride Breath Testmentioning
confidence: 93%
“…Over the last decade, the test meal has been standardized, and the normal 6 h cumulative 13 C recovery rate is approximately 27-29 % [24,25]. Although age and gender do not influence the test results, even moderate exercise can increase or decrease the results [26,27].…”
Section: C-mixed Triglyceride Breath Testmentioning
confidence: 99%
“…Equally, while European guidelines have recommended the use of the C13 mixed triglyceride breath test as an alternative to faecal elastase testing, it is not widely available with poor sensitivity in mild/moderate disease 204 and therefore not recommended.…”
Section: Tests For Malabsorptionmentioning
confidence: 99%
“…The length of time over which excreted CO 2 is measured, the constituents of the test-meal, and physical exercise may affect results[ 14 ]. An attempt to simplify the 13 C-MTG breath test showed that when cumulative CO 2 excretion is measured over less than 4 h the test loses its specificity, although it remains highly sensitive[ 15 ]. The test may generate false positives in patients with steatorrhoea of non-pancreatic origin, such as those with severe duodenal mucosal disease[ 16 ].…”
Section: Diagnosis Of Pancreatic Exocrine Insufficiencymentioning
confidence: 99%